The Efficacy of Fluency-Based Instruction Model in the Teaching of Reading Comprehension: Evidence from Early English Readers - Muhammad Muhlisin; Ahmed Ayoub; Mohammed Yasser (Bale Jurnal, 2026)
This qualitative case study investigated the efficacy of a fluency-based instructional model in supporting early English readers’ reading fluency and reading comprehension in a real classroom context. The study focused on how core fluency routines such as repeated reading and oral reading with feedback were enacted, how learners’ observable reading behaviors changed over time, and which comprehension difficulties persisted during and after fluency practice. Data were collected through non-participant classroom observations using structured checklists and narrative field notes, complemented by semi-structured interviews with the classroom teacher and learners. Analysis followed an iterative qualitative framework of data condensation, data display, and conclusion drawing and verification, supported by triangulation across data sources. Findings indicate strong evidence of improvement in oral reading accuracy and reading rate, reflected in fewer decoding breakdowns, reduced hesitation, increased self-correction, and smoother sentence-level progression during repeated reading cycles. Moderate improvement was observed in prosody, particularly when teacher modeling and feedback emphasized phrasing and punctuation as cues for meaning. Comprehension gains were more selective: learners demonstrated modest growth in literal comprehension, especially on texts with familiar vocabulary and clear structure, while higher-level comprehension such as inference-making and cross-sentence integration remained limited. Persistent barriers included restricted academic vocabulary, weak morphological awareness, difficulties parsing complex syntax, weak cohesion and reference tracking, background knowledge gaps, and limited comprehension monitoring strategies. Overall, the study suggests that fluency-based instruction effectively strengthens oral reading fluency but supports comprehension most consistently when integrated with explicit vocabulary development, sentence-level unpacking, cohesion instruction, schema activation, and strategy training for monitoring and repair.